Not One Step Back: Lessons Learned and Challenges in a Consolidate Agenda of Sexual and Reproductive Rights in the Inter-American Court of Human Rights - Ronconi, Liliana (The Age of Human Rights Journal, 2024)
There have been advances in Latin America regarding the recognition of sexual and reproductive rights, especially in relation to disadvantaged groups such as women and LGBTI persons. In this sense, it is relevant to mention the recognition by the Inter-American System of the right to health as a true right. Nevertheless, there are still many challenges to be faced. In this paper, I will review the progress and challenges of the Inter American Court of Human Right in sexual and reproductive health rights, looking to offer a panoramic overview from a global south perspective by analyzing specific cases. I will then highlight some achievements and setbacks in this area, focus on the impact of these cases in the region and criticize some of the Court’s limited responses.